Assessment of the Impact of Household Income on Child Labour in Bauchi State, Nigeria - Musa, Ibrahim (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2024)
This study examines the impact of household income on child labour in the Bauchi Local Government Area of Bauchi State. The study employs the use of a survey research design through questionnaires. Data were obtained from 50 respondents who reside in the Bauchi Local Government Area of Bauchi State. The study makes use of percentage analysis and chi-square for data analysis and tables for data presentation. The result shows that low household income and lack of economic opportunities are the major determinants of child labour in the area, with an inverse relationship between household income and child labour. The research finds that a large majority of respondents (80%) do not receive grants or support from the government. Therefore, the study recommends policies that will provide more employment opportunities and household income schemes.